Precise determination of mini railway track with ground based laser scanning - Meng, Xiaolin; Liu, Chun; Li, Nan; Joe, Ryding (Taylor & Francis, 2014)
In order to determine the relative or absolute railway track and foundation deformation, ground-based laser scanning technology is utilised in this study to attain a precise 3D track reference. Located at the University of Nottingham’s Innovation Park, the newly built Nottingham Geospatial Building, where the Nottingham Geospatial Institute is based, has a roof laboratory that has unique testing facilities. This includes a mini railway track of 120m in length and other long-term monitoring monuments. A test was performed to precisely determine the ground-truth location of the railway track using a phase-based laser scanner for the formation of a standard reference. A real three dimensional mesh of the laser scanning data forms the basis for the line extraction. The compactly supported radial basis function (CS-RBF) was employed to determine the track features based on a 3D mesh approach. To verify the achievable accuracy of laser scanning technology, ground truth points measured with geodetic methods are compared with the extracted sample points and the results are presented in this paper.